A Fuzzy Logic Approach to Adaptive Data Rate for Mobile LoRaWAN Environments - Sarmento Neto, Geraldo A.; Silva, Thiago A. R. da; Abreu, Pedro F. F.; Veloso, Artur F. Da S.; Mendes, Luis H. De O.; Reis Junior, José V. dos (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2024)
LoRaWAN is a prominent technology designed for wireless communication over long distances, particularly suited for Internet of Things applications. A critical feature of Lo-RaWAN is its Adaptive Data Rate (ADR) mechanism, which optimizes network performance by adjusting transmission parameters. However, the standard ADR scheme often struggles in dynamic environments, particularly with mobile end devices. To overcome this limitation, this work introduces Fuzzy logic based ADR for Mobility (FADR-M), a novel ADR approach incorporating fuzzy logic to adaptively adjust transmission parameters, specifically addressing the challenges of mobility in Lo-RaWAN networks. The proposed solution was evaluated through comprehensive simulations involving various ADR schemes in scenarios considering both static and mobile devices. The results demonstrated the superior performance of FADR-M, with an increase in average PDR of approximately 22% and a reduction in average network energy consumption of around 6J compared to standard ADR in a simulation instance with 1000 mobile devices. In this same scenario, the proposed scheme proved to be energy efficient, achieving an improvement of approximately 120 bits/J compared to other schemes. Therefore, the findings suggest that the proposed FADR-M scheme is highly effective for enhancing network reliability and energy efficiency in LoRaWAN, particularly in environments with high mobility.